Indirect costs: the perverse consequences of Aotearoa New Zealand’s research overheads system - Truax, Olivia; Penney, Camilla; MacDonell, Shelley (New Zealand Science Review, 2025)
Aotearoa New Zealand prides itself on achieving remarkable outcomes with limited resources and embraces a national identity rooted in innovation, resilience, and efficiency. But even number-8 wire can snap. As newly appointed academics navigating the country's research landscape, we have encountered a funding system stretched beyond its limits - one that threatens the integrity and sustainability of the research it is meant to support. Here, we argue that a central issue in the current system is Aotearoa's heavy reliance on indirect cost recovery - or "overheads" - to fund core institutional functions. We explore how this internationally anomalous system undermines research excellence by incentivizing budget-driven project design, fragmenting researchers' time, obstructing career development for early career researchers, and destabilizing institutional budgets through volatile, grant-dependent income. At a time when colleagues in Public Research Organizations - formerly Crown Research Institutes - face job insecurity and uncertainty, we feel obligated to speak out, in line with our role as the "critic and conscience of society" (Education and Training Act, 2022). As the nation restructures its public research system, we argue that core institutional funding must be decoupled from competitive research grants, which should be dedicated to supporting the direct costs of research.